TINGKAT DAYA TAHAN OTOT TUNGKAI SISWA PADA EKSTRAKURIKULER FUTSAL - Gumilar Armawijaya; Hendra Rustiawan; Adang Sudrazat (Wahana Pendidikan, 2021)
This study aims to determine how to know the level of leg muscle endurance of students in futsal extracurricular. The research method used was ex-post facto. The population of this studied was the male students of MAN 3 Ciamis Regency in extracurricular futsal class X and XI, totaling 40 participants. The research instrument used to collect data was the wall squat test. Based on data analysis using SPSS series 24, the results of data processing consist of 1. There was a significant effect of the class X futsal extracurricular group on leg muscle endurance in students of MAN 3 Ciamis, 2. There was a significant influence on the class XI futsal extracurricular group of students on Leg muscle endurance in students of MAN 3 Ciamis, 3. There was a difference between the X class futsal extracurricular group and the XI futsal extracurricular group on the leg muscle endurance in students of the MAN 3 Ciamis. Conclusion: The class X futsal extracurricular group and the class XI futsal extracurricular group had a significant effect on increasing leg muscle endurance in MAN 3 students, Ciamis. Suggestion: This research is expected to be a source of reference for other researchers so that research in the same field is growing, especially in increasing leg muscle endurance.Penelitian ini bertujuan untuk mengetahui seberapa besar tingkat daya tahan otot tungkai siswa pada ekstrakurikuler futsal. Metode penelitian yang digunakan adalah ex-post facto. Populasi penelitian ini adalah siswa putra MAN 3 Kabupaten Ciamis kelas ekstrakurikuler futsal kelas X dan kelas XI yang berjumlah sebanyak 40 orang. Instrumen penelitian yang digunakan untuk mengumpulkan data adalah wall squat test. Berdasarkan analisis data menggunakan SPSS serie 22, hasil pengolahan data terdiri dari 1. Terdapat pengaruh yang signifikan kelompok ekstrakurikuler futsal kelas X siswa terhadap daya tahan otot tungkai pada Siswa MAN 3 Kabupaten Ciamis, 2. Terdapat pengaruh yang signifikan kelompok ekstrakurikuler futsal kelas XI siswa terhadap daya tahan otot tungkai pada Siswa MAN 3 Kabupaten Ciamis, 3. Terdapat perbedaan antara kelompok ekstrakurikuler futsal kelas X dengan kelompok ekstrakurikuler futsal kelas XI terhadap daya tahan otot tungkai pada Siswa MAN 3 Kabupaten Ciamis. Saran : Penelitian ini diharapkan menjadi salah satu sumber referensi bagi peneliti lain agar penelitian pada bidang yang sama semakin berkembang terutama pada peningkatan daya tahan otot tungkai.